Caminhos metodológicos no processo de ensino-aprendizagem de inglês para o acadêmico visual sob as lentes bakhtinianas : possibilidades e construções - Gonçalves, Márcia de Moura (2019)
This study aims at promoting a dialogue involving research in the fields of Applied Linguistics, Foreign Languages (FL), and Inclusive Education for Deaf/HH/visuals, according to Duarte (2016). For this, as our main objective, we proposed to investigate the inclusive classroom, mediated by LIBRAS (the Brazilian Sign Language), having discourse genres in English as our teaching object (DOLZ, SCHNEWULY, 1996). Our specific aims were to identify the visual subjects’ needs and possibilities of learning that would inform us about teaching English as a foreign language; to investigate to what extent the adoption of discourse genre as a teaching object would offer meaningful verbal exchanges that promoted the learning of English, and; to discuss which aspects from the analyzed pedagogical actions might contribute to the formulation of a enunciative-discursive approach of teaching a FL to a visual subject. Based on the Dialogical Analysis of the Discourse (BRAIT, 2006), we examined different kinds of registers obtained throughout the “English Course for the Deaf Student", in Higher Education, which had the attendance of 7 students of the LIBRAS Language Program, 5 visuals, and 2 hearing participants. We carried out analyses of the following kinds of data: utterances made by teachers in a team; utterances designed in face-to-face interactions, and; utterances made by the students. These utterances are discussed in the light of Bakhtinian and Vygotskian studies in dialogical relation with research studies about English teaching for the Deaf/HH that has been conducted in Brazil and in other English Language Teaching contexts. The use of LIBRAS as the mediator in teaching, the use of written Portuguese in the relationship word/reference, the responsive alternation among the participants of the course and the dimension of visuality should be at the base of the pedagogical organization. In the initial level A1, the discourse genres in written English provided the learning of the linguistic structures in the target language and promoted interactions which favored the dialogical relations beyond language learning. Lesson planning under a dialogical and historical-cultural approach implies providing the student with the means to appropriate the different discourse genres which take place in different kinds of utterances. Also, the classroom should continually foster dialogical constructions and the respect for alterity.